Theoretical foundations of the pedagogical project of a Medicine course in the outback of the state of Paraíba, Brazil: contributions to the debate on medical education - Henrique Gonçalves Dantas de Medeiros; Thiago Gomes da Trindade
Abstract Considering the reform of medical education, it is necessary to study experiences that have arisen recently. Therefore, the pedagogical project of the medicine course of Universidade Federal de Campina Grande in Cajazeiras (Paraíba, Brazil) was analyzed in order to recognize its theoretical foundations. It is a qualitative research, descriptive and exploratory, in which indirect documentation and intensive direct observation were used for data collection, and the hermeneutic-dialectical method was utilized for the analysis. Based on presuppositions related to Rural Medicine, the project is eclectic: it encompasses Historical and Dialectical Materialism through Latin American Critical Epidemiology and Problematization Methodology; having the Pedagogy of Competencies as reference, it approaches rationalist, individualist and neopragmatist schools of thought; finally, it converses with Oppositional Postmodernism and Complex Thought. Seeking to overcome the Flexnerian paradigm, the project approaches the Paradigm of Integrality, but faces difficulties to materialize, for which practical proposals are made.